Enforcement of Applicable Laws in Society in The Context of National Criminal Law in Indonesia - Happy Sunaryanto; Kurniawan Tri Wibowo (Universitas Amikom Purwokerto, 2025)
Executive intervention in criminal justice arises as a result of a constitutional design that places the President in a strategic position in the chain of law enforcement, including through prerogative powers such as amnesty, abolition, clemency, and rehabilitation, as well as administrative control over the police and prosecutor's office. This study examines the intervention of executive power in the criminal justice process in Indonesia and its impact on the independence and integrity of judicial institutions. The analysis shows that this authority opens up legal and political space for the executive to influence the process of investigation, prosecution, and correction of court decisions. The cases of Hasto Kristiyanto, Tom Lembong, and Ira Puspadewi show how intervention can cause controversy, create inequality in legal treatment, and create precedents that threaten the principle of the rule of law. The impact not only undermines the due process of law, but also lowers public trust, weakens the morality of the judiciary, and strengthens the perception that the law is in favor of power. These findings encourage the need for stricter, more transparent, and accountable normative restrictions on the use of prerogative authority, as well as the strengthening of oversight mechanisms and the integrity of law enforcement agencies so that the judiciary remains a bastion of justice that is free from political influence.